ICT infrastructure based on intent-based network and service orchestration - Jie ZHANG; Jianhong XU; Yongjian ZHAO; Yunxiang GAO; Xun CHEN (Dianxin kexue)
Considering the complexity of communication networks and the requirement of communication business innovation, operators should upgrade their ICT infrastructure.Based on the study of intent-based network and service orchestration technology, a new ICT architecture that combines the automatic transformation of business intention and the automatic correlation of network service models were proposed.As an automatic and intelligent upgrade of the operator BOSS IT system, it aims to accelerate the process of comprehensive digital transformation of operators.